Mitzvah girls : bringing up the next generation of Hasidic Jews in Brooklyn - Fader, Ayala, 1964- (Anthropology online., 2009)
Mitzvah Girls is the first book about bringing up Hasidic Jewish girls in North America, providing an in-depth look into a closed community. Ayala Fader examines language, gender, and the body from infancy to adulthood, showing how Hasidic girls in Brooklyn become women responsible for rearing the next generation of nonliberal Jewish believers. To uncover how girls learn the practices of Hasidic Judaism, Fader looks beyond the synagogue to everyday talk in the context of homes, classrooms, and city streets. Hasidic women complicate stereotypes of nonliberal religious women by collapsing disti.